2011
DOI: 10.1371/journal.pntd.0001152
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations Associated with Neurocysticercosis: A Systematic Review

Abstract: BackgroundThe clinical manifestations of neurocysticercosis (NCC) are poorly understood. This systematic review aims to estimate the frequencies of different manifestations, complications and disabilities associated with NCC.MethodsA systematic search of the literature published from January 1, 1990, to June 1, 2008, in 24 different electronic databases and 8 languages was conducted. Meta-analyses were conducted when appropriate.ResultsA total of 1569 documents were identified, and 21 included in the analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
273
2
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(301 citation statements)
references
References 45 publications
10
273
2
16
Order By: Relevance
“…Seizures are the most frequent manifestations of NCC (70-90%) followed by headache (38%), focal deficits (16%), and signs of intracranial hypertension (ICH, 12%). Other manifestations occur in fewer than 10% of symptomatic patients 13 . Recent Brazilian investigations have reported that NCC seems to contribute to or even cause refractory epileptic seizures associated with hippocampal sclerosis 8,9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seizures are the most frequent manifestations of NCC (70-90%) followed by headache (38%), focal deficits (16%), and signs of intracranial hypertension (ICH, 12%). Other manifestations occur in fewer than 10% of symptomatic patients 13 . Recent Brazilian investigations have reported that NCC seems to contribute to or even cause refractory epileptic seizures associated with hippocampal sclerosis 8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical manifestations of NCC are variable and strongly depend on the number, type, size, location, and stage of development of the cysticerci, as well as the immune response of the host against the parasite 12,13,14,15,16 . Seizures are the most frequent manifestations of NCC (70-90%) followed by headache (38%), focal deficits (16%), and signs of intracranial hypertension (ICH, 12%).…”
Section: Discussionmentioning
confidence: 99%
“…The main clinical feature, however, lies in human cysticercosis. The development of cysticerci in the central nervous system (neurocysticercosis, NCC) is shown to be an important cause of acquired epilepsy and other neural disorders in endemic regions (Carabin et al, 2011). In recent years, it has become clear that the disease complex is not only of importance in the African and American continents (Flisser et al, 2006), but also in Asian countries, such as Nepal (Joshi et al, 2004;Rajshekhar et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…En una revisión sistemática de estudios publicados entre 1990 y 2008, Carabin, et al, encontraron, en orden de frecuencia, las siguientes manifestaciones clínicas: convulsiones o epilepsia (79 %), cefalea (40 %), déficit neurológico focal (16 %) y signos de hipertensión intracraneal (12 %), en tanto que, en menos del 10 % de los casos, se presentaron ataxia, alteraciones visuales, parálisis de nervios craneales, síntomas meníngeos y las alteraciones del estado mental (8,9).…”
unclassified